Lineages and Advancements in Material Culture Studies Perspectives from UCL Anthropology - Carroll, Timothy; Walford, Antonia; Walton, Shireen (Taylor & Francis, 2021)
This volume comprises a curated conversation between members of the Material Culture Section of University College London Anthropology. In laying out the state of play in the field, it challenges how the anthropology of material culture is being done and argues for new directions of enquiry and new methods of investigation. The contributors consider the ramifications of specific research methods and explore new methodological frameworks to address areas of human experience that require a new analytical approach. The case studies draw from a range of contexts, including digital objects, infrastructure, data, extraterrestriality, ethnographic curation, and medical materiality. They include timely reappraisals of now-classical analytical models that have shaped the way we understand the object, the discipline, knowledge formation, and the artefact.